Highly efficient flotation separation of wolframite from calcite using a dual-ligand hydroxamic acid collector: Experiment insight and mechanism exploration - Ma, Jinpeng; Huang, Zhiqiang; Safarov, Sayfidin; Xu, Fengping; Che, Wenfang; Yang, Xiaowen; Peng, Jianping; Zhong, Hong; Chen, Xiangping; Wang, Hongling; Ma, Xin; Cheng, Chen; et al. (Colloids and surfaces. A, Physicochemical and engineering aspects, 2026)
Aiming at the problems of traditional collectors in the flotation of tungsten ore, such as weak collecting ability for wolframite and difficulty in effective separation from calcium-bearing gangue (e.g., calcite), a dual-ligand hydroxamic acid surfactant, sebacoyl hydroxamic acid (SHA), was synthesized and used as the high-efficiency collector for wolframite enrichment in this study. Compared with the traditional collector benzhydroxamic acid (BHA), SHA exhibited stronger collecting ability for wolframite and better selectivity towards calcite. Micro-flotation tests indicated that at pH = 8, using 100 mg/L SHA achieved the recoveries of 90 % for wolframite and merely 48 % for calcite. Artificial mixed mineral flotation tests demonstrated that SHA yielded a wolframite concentrate with WO3 grade of 61.01 % and WO3 recovery of 94.98 %, markedly outperforming the flotation concentrate obtained from BHA. Contact angle measurements confirmed that SHA could significantly enhance the surface hydrophobicity of wolframite. Fourier transform infrared spectroscopy (FT-IR) and ζ-potential measurements exhibited that SHA had a stronger chemisorption affinity to wolframite than calcite. X-ray photoelectron spectroscopy (XPS) and density functional theory (DFT) calculations indicated that the double -CONHOH groups in SHA molecule could chelate with the Fe sites on wolframite surface to form five-membered rings. Compared with BHA, SHA had stronger chemical reactivity and van der Waals forces onto wolframite. Thus, SHA was a potential choice for the efficient separation and enrichment of wolframite from calcite, which could further promote the production of tungsten metal. [Display omitted] •A dual-ligand hydroxamic acid SHA was used as collector in the wolframite flotation.•SHA exhibited stronger collecting ability for wolframite compared with BHA.•SHA had double action sites for the adsorption on wolframite surface.•SHA was a potential candidate to promote the recovery of tungsten resources.